Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1146/annurev.ecolsys.30.1.479
|View full text |Cite
|
Sign up to set email alerts
|

Do Plant Populations Purge Their Genetic Load? Effects of Population Size and Mating History on Inbreeding Depression

Abstract: ▪ Abstract  Inbreeding depression critically influences both mating system evolution and the persistence of small populations prone to accumulate mutations. Under some circumstances, however, inbreeding will tend to purge populations of enough deleterious recessive mutations to reduce inbreeding depression (ID). The extent of purging depends on many population and genetic factors, making it impossible to make universal predictions. We review 52 studies that compare levels of ID among species, populations, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
550
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 502 publications
(569 citation statements)
references
References 186 publications
10
550
2
2
Order By: Relevance
“…Byers and Waller, 1999;Hedrick and Kalinowski, 2000;Keller and Waller, 2002) and threatens the survival of small populations, both wild and captive. However, since inbreeding increases the frequency of the deleterious homozygous genotype, selection against deleterious alleles is also increased during inbreeding (Crow and Kimura, 1970), thereby providing an opportunity for a population to be 'purged' of its mutational load (Lande and Schemske, 1985;Barrett and Charlesworth, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Byers and Waller, 1999;Hedrick and Kalinowski, 2000;Keller and Waller, 2002) and threatens the survival of small populations, both wild and captive. However, since inbreeding increases the frequency of the deleterious homozygous genotype, selection against deleterious alleles is also increased during inbreeding (Crow and Kimura, 1970), thereby providing an opportunity for a population to be 'purged' of its mutational load (Lande and Schemske, 1985;Barrett and Charlesworth, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Saccheri et al, 1996;Lacy and Ballou, 1998;Byers and Waller, 1999;Swindell and Bouzat, 2006), selection in these studies was fairly intense and it would be inappropriate to extrapolate directly to populations of conservation concern. For example, zoo conditions are often benign and hence the selection they exert may not be sufficient to cause purging (but see King, 1939;Gilligan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The endogamic depression observed in P. corcovadensis is usually found in predominantly allogamous plant populations (Wiens et al 1987, Husband & Schemske 1996, Byers & Waller 1999. Here, despite the intense presence of unviable seeds or infertile ovules, higher germination percentages were obtained by self-pollination and geitonogamy originated seeds.…”
Section: Resultsmentioning
confidence: 83%
“…Indeed, we detected no purge of ID at this short time scale. The effectiveness of purging is not frequently observed in plant populations, even when inbreeding occurs (Byers and Waller, 1999). Comparing selfed and crossed progenies obtained in a natural population of P. sylvestris, Koelewijn et al (1999) observed an effect of ID on survival and seed set up to an age of 23 years, but no significant differences in height and flowering, indicating that high levels of ID both for early stage (seed production) and later stages of the life cycle were maintained in the population in the long run.…”
Section: Effects Of Selfing On Germination and First Year Growth In Nmentioning
confidence: 99%
“…Effective purging of inbreeding depression (ID) depends not only on the mating system that generates inbred individuals but also on the genetic make-up of ID (Byers and Waller, 1999). ID that is caused by a small number of recessive genes that have major deleterious effects on fitness is expected to vary among individuals depending on their genotype at these few major genes and, therefore, to respond rapidly to selection.…”
Section: Introductionmentioning
confidence: 99%